Study on the problems that influence the success contractor in Kuantan - Suhaiza, Subri (2014)
The construction industry was sector that contributed to the country economy. A building project when implemented involves many stages and various parties. All projects normally planned to be completed on schedule and within the expected cost and quality. The failure of the contractor to complete projects that result in abandoned, particularly involving government projects particularly mega projects. Therefore, the contractors should be aware of the problem and the factors that influence success in the completion of the construction project. The objectives of the study are to identify the main problems that influence the success contractor in completing the construction, to determine the major factors that influence the successful completion of construction project and to analyses the impact of the problems in construction projects to contractors. A total of 66 sets of questionnaires were distributed to the contractor and 42 completed questionnaires have been received. The data is analyzed using Relative Index (RI). The main problems that influence the success contractor in completing the construction are problem in financial, time, cost, material and problems occur during construction. The major factors that influence the successful completion of construction project are contractor, project team and client. The impact of the problems in construction projects to contractors are delay in project completion, increased cost, cash flow and financial disruption.